Analisis Model Kepemimpinan Kepala Sekolah dalam Meningkatkan Kinerja Guru - Zannatul Wahdah; Ahmad Tohardi; Ajat Sudrajat (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
This research aims to analyze the role and leadership model of the school principal in managing the implementation of the main duties of teachers at SMP Negeri 3 Sepauk District, Sintang Regency. This type of research is research with a case study approach. The results of this research show that the principal's exemplary leadership in influencing teacher performance at SMP Negeri 3 Sepauk District, Sintang Regency, where the role of the principal in influencing educational policy in the school prioritizes the discipline of teachers and students who do not use arrogant but humanist methods. with discipline, the education and learning process at school can be achieved well so that it can produce graduates by the school's goals. The principal's exemplary leadership in influencing teacher performance in State Middle Schools. The principal's good example of leadership in influencing teacher performance in State Middle School 3, Sepauk District, Sintang Regency, where the principal's task in directing the process of educational regulation in schools regarding teacher performance generally involves teachers or teachers. to participate in preparing or coaching which aims to increase teacher understanding and abilities to improve teacher performance for students at SMP Negeri 3 Sepauk District in achieving good learning achievements. Keywords: Leadership Model, Principal, Teacher Performance.